Carbon monoxide dissociative attachment and resonant dissociation by electron-impact. (13th January 2016) - Laporta, V; Tennyson, J; Celiberto, R
Abstract: Low-energy dissociative electron attachment and resonant electron impact dissociation of CO molecule are considered. Ro-vibrationally resolved cross sections and rate coefficients for both the processes are calculated using an ab-initio model based on the low-lying resonance of CO − . Final results show that the cross sections increases very rapidly as a function of the ro-vibrational level; these cross sections should be useful for understanding kinetic dissociation of CO in strongly non-equilibrium plasmas.